Studying the Relationship between some Biokinematic Variables and some Physical Measurements with the Level of Achievement in 25-meter Freestyle Swimming - Ibraheem, Dhiaa Zaki; Abood, Nawaf Owaid; Hammo, Falah Taha (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. Swimming experienced significant growth and achievement in the late twentieth century and early second millennium, marked by the creation of advanced records. This progress is due to rigorous training, practical experience, and the utilization of modern scientific techniques and applied sciences such as biomechanics. This study aims to evaluate several bio-kinematic variables, physical measurements, and completion times in 25-meter freestyle swimming. Materials and methods. Researchers used a descriptive approach to suit the nature of the research. The research sample consisted of 6 swimmers in the Nineveh Governorate applicant category. There was a digital camera with a speed of 60 images/second. Results. There is a positive significant correlation between the anthropometric variable (arm length) with the total time. The researchers attribute this to the fact that the length of the distance of one stroke in swimming (25) meters depends primarily on the length of the total arm and thus, which will lead to covering the total distance of completion in the shortest possible time, given that the length of the arm is part of the length of the stroke. Conclusion. The researchers concluded that the bio-kinematic variables studied played a very important role in achieving the best sample performance, even though the sample performance was generally poor. The large number of arm strokes in the study sample led to an increase in stroke frequency at the expense of decreasing the average length of arm strokes, thereby increasing completion time.